2019
DOI: 10.4103/jpbs.jpbs_211_18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist-directed counseling and message reminder services on medication adherence and clinical outcomes in type 2 diabetes mellitus

Abstract: Introduction: Medication nonadherence is the most common issue observed in the management of diabetes because of complex and lifelong therapy. The study aimed to assess the effect of pharmacist-directed counseling and daily text message reminder on medication adherence and clinical profile of patients with type II diabetes. Materials and Methods: This prospective, open-labeled, randomized control trial was carried out in outpatient medical department of a secondary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 17 publications
5
45
0
Order By: Relevance
“…For this parameter, the difference in change between both groups ranged from +2.1 mg/dL to -27 mg/dL, and was reported as statistically significant in only seven studies (33.3%). 27 , 29 , 35 , 39 , 40 , 45 , 57 …”
Section: Resultsmentioning
confidence: 99%
“…For this parameter, the difference in change between both groups ranged from +2.1 mg/dL to -27 mg/dL, and was reported as statistically significant in only seven studies (33.3%). 27 , 29 , 35 , 39 , 40 , 45 , 57 …”
Section: Resultsmentioning
confidence: 99%
“…performed by pharmacists such as care coordination, medication review and counseling, and prescription suggestions to physicians [28,[33][34][35]37,38,41,42,47,48,50,51,55,57]. All pharmacist task-sharing interventions incorporated diabetes self-management education, but no trial included education alone.…”
Section: Plos Medicinementioning
confidence: 99%
“…All pharmacist task-sharing interventions incorporated diabetes self-management education, but no trial included education alone. Seven interventions included counseling and reminders through telephone calls or text messages [34,35,38,39,41,55,57], and a study in Iran incorporated only telephone calls with no face-to-face encounters [50]. No intervention involved pharmacists independently prescribing or titrating medications.…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…A mobile phone text message can serve as a simple and cost-effective option in improving medication adherence and clinical outcomes by providing information between clinic visits has been reported [73,74]. A report from the National Diabetes Commission suggested that an inappropriate attitude of health care professionals toward diabetes could lead to poor patient outcomes [75]. In educational program, a clinical or community pharmacist can improve adherence by providing medication consultation service, creating an individualized patient schedule on administration times and dosage of each medication, educating the patient on the importance of medication adherence, dietary adherence and exercise on better glycemic control, giving advice on how to reduce adverse effects of medications, and also by teaching how to take medications in the holy month of Ramadan or other religious fasting, and how to use pill boxes and diary logs to reduce forgetfulness.…”
Section: Diabetes Carementioning
confidence: 99%